Eco-efficient Construction and Building Materials - Pacheco Torgal, Fernando; Jalali, Said (Springer London, 2011)
Eco-efficient Construction and Building Materials provides essential reading about materials for the construction industry in the twenty-first century. It covers the latest findings in the field, especially the toxicity aspects, embodied energy, construction and demolition wastes, the use of wastes in concrete, masonry units, materials reinforced with vegetable fibres, earth construction, the durability aspects, and also the importance of nanotechnology to the development of more environmentally-friendly materials. Based on more than nine hundred references, Eco-efficient Construction and Building Materials is of fundamental importance to academics, engineers and architects who are dedicated to the creation of a greener and more holistic construction industry.